Roy Cape : a life on the calypso and soca bandstand - Guilbault, Jocelyne; Cape, Roy, 1942- (Duke University Press, 2014)
Part ethnography, part biography, and part Caribbean music history, Roy Cape is about the making of reputation and circulation, and about the meaning of labor and work ethics. An experiment in storytelling, it joins Roy''s voice with that of ethnomusicologist Jocelyne Guilbault.